Chemical Machining of St37 Rod Using Etchant Substance FeCl3 - Cakir, O. (POLISH ACAD SCIENCES INST PHYSICS, 2019)
Chemical machining is one of the oldest nontraditional machining processes. It applies chemical etchant to machine material. The method is very basic and economical to produce complex geometrical parts from thin sheet materials. The application of this method to cylindrical parts is not common. In this study, chemical machining process was employed to machine rod as cylindrical part. The selected material was St37 with diameter of 10 mm. The experimental study implemented ferric chloride, which is known a universal chemical etchant for iron-based materials, at three different etchant solutions in two chemical machining temperatures (30 degrees C and 50 degrees C). The experimental setup is based on upright drilling machine that has three different spindle speed values (250, 500, and 1500 rpm). It was observed that lower etchant concentration provided higher diameter reduction, surface roughness, and cylindricity. Moreover, the effect of chemical machining temperature is examined and increase of this value produced faster machining.
Keywords: Physics